Long Intergenic Nonprotein Coding RNA 00174 Aggravates Lung Squamous Cell Carcinoma Progression via MicroRNA-185-5p/Nuclear Factor IX axis. (25th August 2022) - Gu, Peipei; Lin, Lin
Abstract : Extensive studies have presented that long noncoding RNAs (lncRNAs) are closely implicated in the pathogenesis of various human malignancies, including lung squamous cell carcinoma (LUSC). This study explored the biological role and the underlying mechanism of long intergenic nonprotein coding RNA 00174 (LINC00174) in LUSC. LINC00174 expression was measured by reverse transcription quantitative real-time polymerase chain reaction (RT-qPCR). Both in vitro and in vivo experiments were conducted to determine LINC00174 function in LUSC. Mechanical assays were performed to investigate the molecular mechanism involving LINC00174 and related genes. LINC00174 expression was high in LUSC cells. Silencing of LINC00174 could restrain LUSC cells proliferation, migration, and invasion while promoting cell apoptosis. Mechanically, LINC00174 could interact with miR-185-5p to upregulate nuclear factor IX (NFIX), which was the direct target gene of miR-185-5p. Notably, NFIX elevation could rescue the repressing effect of LINC00174 silence on LUSC cell malignant behaviors. Our data suggested that LINC00174 aggravated LUSC progression via serving as a competing endogenous RNA (ceRNA) to sponge miR-185-5p and ultimately upregulate NFIX, which offered a promising novel target for LUSC therapy.